Peran ECPAT dalam Menangani Eksploitasi Seksual Komersial Anak di Indonesia - Millatina, Amila Hasya; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Indonesia is very famous as a tourist destination for many countries in the world. Thetourism sector is one of the largest contributors of foreign exchange for Indonesia, but inaddition there is a problem that is caused by the crime of commercial sexual exploitationof children. As long as the government campaigns for the tourism sector as one of themainstay sectors to increase the country’s foreign exchange, the government is consideredless ready to supervise various activities and tourism networks so that the crime of sexualexploitation of children takes place in Indonesia. Considering the phenomenon, ECPAT asan international organization engaged to oppose cases of commercial sexual exploitationcrimes of children take a role in the handling of such cases. This research uses the conceptof Civil Society Organization (CSO) which is explained by Boussard (2003) role ofECPAT as agenda setter, educator, and as counterparts. Through this role can be seen theinvolvement of ECPAT in handling cases of commercial sexual exploitation of children inIndonesia.